Creativity and Culture as Elements of Urban Development - Weiler, Fabiane Frois B (2017)
Abstract: cities are the picture of the outbreak of expressions of the processes of accumulation, consumption, circulation and production of goods plus the interaction of individuals, socially represented in classes. In general, from the adjectives and their derivations a city is constructed that articulates through its actors in constructing itself locally viable. From this perspective, this essay aims to analyze, briefly, the relations between urban development and creative economy. For this, methodologically, it is worth of a bibliographical revision about the fundamental concepts of the urban development and creative economy and repercussions of this relation. In this line, it is thought that the city when it uses creativity as an adjective must be conceived in a logic of space built to meet the particularities of the territory. And, not for the logic of competition and standardization of territory designed for global competition. The purpose of culture and creativity must break with dependence in the context of development, especially as regards the way and process as the city and its urbanization are constituted and consolidated.A Criatividade e a Cultura como Elementos do Desenvolvimento UrbanoResumo: as cidades são o retrato da eclosão das expressões dos processos de acumulação, consumo, circulação e produção de bens somados a interação de indivíduos, socialmente representados em classes. Em geral, a partir dos adjetivos e suas derivações se constrói uma cidade que se articula por meio de seus atores em construir-se viável localmente. Nessa perspectiva, este ensaio visa analisar, sucintamente, as relações entre desenvolvimento urbano e economia criativa. Para tal, metodologicamente, vale-se de uma revisão bibliográfica acerca dos conceitos fundamentais do desenvolvimento urbano e economia criativa e repercussões dessa relação. Nessa linha, pensa-se que a cidade quando emprega a criatividade como adjetivo deve ser concebida numa lógica do espaço construído para atender as particularidades do território. E, não para a lógica da competição e padronização do território pensada para a competição global. O propósito da cultura e da criatividade deve romper com a dependência no contexto do desenvolvimento, especialmente, no que tange ao modo e processo como a cidade e sua urbanização se constituem e consolidam.La Creatividad y la Cultura como Elementos del Desarrollo UrbanoResumen: las ciudades son el retrato de la eclosión de las expresiones de los procesos de acumulación, consumo, circulación y producción de bienes sumados a la interacción de individuos, socialmente representados en clases. En general, a partir de los adjetivos y sus derivaciones se construye una ciudad que se articula por medio de sus actores en construirse viable localmente. En esta perspectiva, este ensayo pretende analizar, sucintamente, las relaciones entre desarrollo urbano y economía creativa. Para ello, metodológicamente, se vale de una revisión bibliográfica acerca de los conceptos fundamentales del desarrollo urbano y economía creativa y repercusiones de esa relación. En esa línea, se piensa que la ciudad cuando emplea la creatividad como adjetivo debe ser concebida en una lógica del espacio construido para atender las particularidades del territorio. Y, no para la lógica de la competición y estandarización del territorio pensada para la competición global. El propósito de la cultura y la creatividad debe romper con la dependencia en el contexto del desarrollo, especialmente en lo que se refiere al modo y proceso como la ciudad y su urbanización se constituyen y consolidan.